ANALYSIS OF INTERPRETING TYPES IN NCT'S SPECIAL AWARD VIDEO AT THE INDONESIAN TELEVISION AWARD - Pramudita Ariani; Nabilla Serly Adinda Putri; Ramadan Adianto Budiman (Acceleration: Multidisciplinary Research Journal, 2023)
Language is a social communication tool as a sound symbol system resulting from human speech. Humans, as social beings, need means to interact with other humans in society. The number of languages in this world is an obstacle for some people to communicate. Someone who can help with communication problems is called an interpreter. An interpreter is someone skilled at translating language orally. This research aims to analyze the interpreting technique used by an interpreter in a YouTube video entitled "Pemenang 'Special Award' Indonesian Television Award". This study uses a descriptive analysis method, namely a method that focuses on meaning and results. The data taken is in the form of dialogues or texts. In this study, the authors found one of the interpreting techniques, namely the Consecutive Interpreting Techniques and some of the advantages of these techniques.